Caring With Compassion, Domain 1: U.S. Public Healthcare Systems - Davoren Chick; April Bigelow; Frank Jacob Seagull; Heather Rye; Brent Williams (Association of American Medical Colleges, 2014)
Abstract Introduction Caring with Compassion provides core background information to support clinical care for homeless, underserved, uninsured, and at-risk populations. It was designed by an interdisciplinary team of educators from the fields of medicine, nursing, and social services. The team identified practical knowledge objectives using an iterative, expert consensus approach. Content validity was addressed by incorporating national internal medicine milestones and feedback from national educational leaders. This content is designed for graduate medical learners, advanced medical students, and nurse practitioners. Methods Caring with Compassion is divided into two major content domains: Domain 1 provides an overview of US public health care systems; Domain 2 presents the bio-psychosocial model of health care and special care needs of underserved populations. This submission includes the content for Domain 1: U.S. Public Healthcare Systems. Domain 2 is separately published by MedEdPORTAL. Results Nationally, over 350 learners have registered for the online version of the curriculum, and feedback has been highly positive. Preliminary quantitative outcome data demonstrates highly significant improvement in multiple choice examination scores following exposure to the modules for all assessed content areas [n, pretest, posttest, t test p value]: epidemiology of populations in need (42, 49%, 81%, p < .0001); public health insurance (30, 52%, 80%, p < .0001); health care delivery systems knowledge (19, 53%, 67%, p < .002). Discussion This content has benefited from continual revisions based on learner and faculty feedback, including results of the formal focus groups as detailed above. Expansion of content is ongoing based on requests from faculty users nationally. Further plans include expansion of faculty development tools and continual content revisions based on new research and curricular feedback.